The folding pathway of a protein at high resolution from microseconds to seconds - Nölting, Bengt (The National Academy of Sciences of the USA, 1997)
We have documented the folding pathway of the 10-kDa protein barstar from the first few microseconds at the resolution of individual residues from its well characterized denatured state. The denatured state had been shown from NMR to have flickering native-like structure in the first two of its four α-helices. Φ-value analysis shows that the first helix becomes substantially consolidated as the intermediate is formed in a few hundred microseconds, as does the second to a lesser extent. A native-like structure then is formed in a few hundred milliseconds as the whole structure consolidates. Peptide fragments corresponding to sequences containing the first two helices separately and together as a helix-loop-helix motif have little helical structure under conditions that favor folding. The early stages of folding fit the nucleation–condensation model that was proposed for the smaller chymotrypsin inhibitor 2, which is a single module of structure and folds by two-state kinetics. The early stages of the multistate folding of the larger, multimodular, barnase have proved experimentally inaccessible. The folding pathway of barstar links those of CI2 and barnase to give a unified scheme for folding.